A word on words : the best of John Seigenthaler's interviews - Seigenthaler, John, 1927-2014 (Vanderbilt University Press, 2023)
"For years the legendary John Seigenthaler hosted "A Word on Words," on local public television station, WNPT. He interviewed some of the most interesting and most important writers of our time. Frye Gaillard and Pat Toomay have collected and transcribed some of the iconoclastic interactions on the show"--